Climate-Smart Village roving workshop as a farmer-to-farmer learning platform - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Since 2015, CCAFS has implemented the CSV Roving workshop, which was attended by a total of 135 farmers and researchers. In 2019, a workshop on establishing CSVs in the ASEAN Region, for key officials of the ASEAN Climate Resilience Network member countries, was designed using the roving workshop approach.